Access and Continuity: A Multidisciplinary Education Workshop to Teach Patient-Centered Medical Home (PCMH) Principles - Lauren Block; Christopher Petersen; Daniel J. Coletti; Pratiksha Yalakkishettar; Nancy LaVine (Association of American Medical Colleges, 2020)
Introduction As more practices move to patient-centered medical home (PCMH) models, future health care professionals must train to work in collaborative settings. We implemented a 3-hour workshop for multidisciplinary trainees on the PCMH principles of access and continuity based on the EFECT framework (eliciting a patient-centered narrative, facilitating an interprofessional team discussion, evaluating the clinical evidence, creating a shared care plan, and tracking outcomes). Methods Participants included internal medicine residents and medical, physician assistant (PA), and clinical psychology students. The workshop incorporated reflective activities identifying patient and provider health care delivery priorities, plus a PCMH presentation and group activities focusing on access and continuity. Evaluations were analyzed qualitatively and quantitatively. Results The workshop had 39 participants (seven physicians, one PA, one educator, one psychologist, three staff, nine residents, one PA student, one psychology extern, and 15 medical students). On a 0-10 Likert scale (0 = don't agree at all, 10 = completely agree), learners reported higher knowledge of PCMH principles (M = 8.8), feeling better prepared for PCMH work (M = 8.6), and having obtained real-world skills (M = 8.3). Open-ended responses describing the workshop's take-home message included the role of patient-centeredness in clinical redesign, the value of the multidisciplinary team in optimizing access and continuity, and how to use a quality improvement approach for access and continuity. Discussion This workshop increased PCMH-related knowledge and encouraged discussion of professional roles within the team. Learners recognized the benefits of team-based rather than provider-centric approaches to access and continuity.